Analysis of the sanitary efficiency of the hydraulic works built to decontaminate the Ortega ravine by the EPMAPS, Quito - Enríquez, Carlos (2019)
The current study focuses on analyzing the sanitary efficiency of the hydraulic works constructed to decontaminate the Ortega ravine by the EPMAPS. The rainy and dry seasons where defined based on hydraulic and hydrologic studies performed on the ravine. In order to characterize the physiochemical and microbiological parameters, multiple factors were taken into account such as the current Ecuadorian environmental legislation (Ministerial agreement No 097-A, Annex 1 from book VI, tables 2 and 2-a, Official Record 387, June 4, 2015), and the historic records of the ravine of 2012, 2013, and 2014. Moreover, the study of aquatic macroinvertebrates was carried out through the BMWP index to characterize the water quality running through the Ortega ravine and its tributaries. Three zones of the Ortega ravine were analyzed to define their behavior, they were the upper middle and lower part of it and their environmental implications